“Connect Local”: protocol for the evaluation of a codesigned whole of community approach to promote social connection in older adults - Ogrin, R.; Robinson, E.; Rendell, K.; Alrababah, S.; Fineberg, D.; Fiddes, K.; Yerolemou, A.; Lim, M. H.; Engel, L.; Lowthian, J. A. (Frontiers in Public Health, 2024)
There is wide acknowledgement in the literature that social connection is protective against loneliness and depression. More robust research, however, is needed to evaluate interventions that promote social connection. This protocol paper outlines the evaluation of a community-wide social connection program, Connect Local, in metropolitan Melbourne, Australia to support people 65 years and older to increase access to local community services/activities; and to ascertain impact on social connection, loneliness, depressive symptoms, physical and mental wellbeing, and use of health services.A Type 1 Hybrid design, including program effectiveness, cost-effectiveness, and implementation evaluation of the Connect Local program, will be undertaken.Eighty-eight participants aged ≥65 years with one or more chronic health condition, who are also either experiencing or at risk of loneliness, social isolation and depressive symptoms will be invited to participate in the evaluation. Outcomes, measured at baseline, 3, 6 and 12 months, include loneliness, social isolation, depressive symptoms, social anxiety, goal attainment, wellbeing, quality of life and health care utiliszation. A gender and age matched comparator group of 88 individuals will be recruited from outside the intervention local government area.Impact of the intervention on community service providers in the target region will be evaluated using mixed methods, where triangulation will be used to combine the qualitative and quantitative data using a deductive-simultaneous design. Changes in wellbeing and quality of life of community volunteers will also be measured.All groups will be interviewed to ascertain their experience and perceptions of the program.The economic evaluation will use a Social Return on Investment (SROI) approach, to include outcomes at the individual, community, and system levels. Implementation outcomes will consider Reach, Adoption, Feasibility, Acceptability, Appropriateness, Fidelity, and Sustainability of the intervention.This study will provide a better understanding of the impacts of a community-wide social connection approach in older adults, the community and broader system.